The Correlation Between Playing Online Game English Version And Students’ English Achievement at Third Grade of Vocational Senior High School 3 Pamekasan - Arisandi Setiyawan; Itsnan Bakhtiar Rifdi (Universitas Islam Madura, 2016)
In this modern era, on line game become trending topic. Generally, most of people receive game development anthusiastically. The fact, the researchers found that there are many people spend their spare time in online game center. Moreover, playing online game English Version can affect the students’ English achievement. By playing online game, the students or players will try to understand the instruction stated using English. They will have many English vocabularies on the game then it will increase the English achievement at the school. This research is correlation design which tries to find the correlation between Playing Online Game English Version and Students’ English Achievement by using Pearson Product Moment formula. The population is the students of the third grade of Vocational Senior High School 3 Pamekasan. which consist of 11 classrooms The result. The number of all class consists of 289 students, then the researcher take 33 students as a sample. The result of this research shows that playing online game has a high/strong correlation to the students’ English achievement of the third grade of Vocational Senior High School 3 of Pamekasan. It is proven by observed rxy (0,739) is higher than “r” table of product moment in significance level 5% (0,344) and 1% (0,442). (0,344) means “r” table value of product moment in significance level 5% of 33 respondent. While (0,442) means “r” table value of product moment in significance level 1% of 33 respondent. And (0,739) get from the computation of data analysis both variable X (playing game online) and variable Y (Students’ English achievement).